The first involved joints and associated factors in patients with rheumatoid arthritis - Mete Pekdiker; Hamdi Oğuzman (Archives of Rheumatology, 2024)
Objectives: This study aimed to investigate the first involved joints and associated factors in Turkish patients with rheumatoid arthritis (RA). Patients and methods: This retrospective cross-sectional study included 300 newly diagnosed and disease-modifying antirheumatic drug-naïve RA patients (240 females, 60 males; mean age: 54±1.2 years; range, 18 to 82 years). Baseline demographic, clinical, and laboratory data were evaluated between January 2022 and December 2022. The patients were divided into four groups according to autoantibody profile: antibody-negative patients (Group 1; both RF and anti-CCP were negative in this group of patients), RF-positive patients (Group 2), anti-CCP-positive patients (Group 3), and patients with dual seropositivity with RF and antiCCP (Group 4). The patients were also divided into two groups according to the size of the first affected joint: patients with SJI at diagnosis and patients without SJI involvement at diagnosis. Results: Rheumatoid factor (RF) and anti-cyclic citrullinated peptide (CCP) antibody positivity rates were 40.3% and 35.6%, respectively. The mean lag time to diagnosis was 25±36 months. At the disease onset, 20% of patients did not have small joint involvement (SJI). Seronegative patients tended to be female (p=0.001), had longer lag time (p=0.001), and had lower levels of C-reactive protein (p=0.025), white blood count (p=0.005), and neutrophil/lymphocyte ratio (p=0.001) compared to the dual seropositive group. Patients presenting with SJI had a younger age (p=0.002), tended to be female (p=0.001), and had lower RF (p=0.034) and anti-CCP (p=0.031) positivity. Only age (p=0.005) and dual seronegativity (RF and anti-CCP; p=0.035) were the independent predictors of SJI in multivariate analysis. Conclusion: The decreasing age and seronegative status were defined as independent risk factors of SJI at the onset of RA. Population-based, prospective studies are needed for earlier diagnosis.